Hijab wearing among Malay women in Malaysia: media or social influence? - A.Manaf, Aini Maznina; Wok, Saodah; Ismail, Rizalawati (2013)
Hijab wearing among Muslim women is currently seen as a common phenomenon in Malaysia. Is the religious awareness among them on the rise? Or is it just a fashion? Many studies (Williams and Vashi, 2007; Furseth, 2011) were carried out to understand factors that influ-ence hijab wearing among Muslim women. Nonetheless, little information is available on the roles that media play in women’s decision to wearing hijab. This study was conducted to find out the perception of Muslim women on the extent to which media and people surrounding them influence their hijab (head cover) wearing. Specifically, the objectives of this study are (1) to find out the patterns of hijab wearing, (2) to find out sources of media influence on hi-jab wearing among Malay women, (3) to determine sources of social/interpersonal influence on hijab wearing among Malay women, (4) to compare between the media influence and the social/interpersonal influence on hijab wearing among Malaysia women, and (5) to analyze the extent of media and social/interpersonal influence on impact change from hijab wearing. Using data from a survey conducted with 362 female students from an Islamic Higher Educa-tion Institution in Malaysia, the findings revealed that Facebook, blog and magazine are the top three highest media influencing on impact change from hijab wearing. Parents, friends/colleagues and siblings have more influence on hijab wearing than the other sources. Social/interpersonal influence has a bigger influence than the media influence on hijab wear-ing. In addition, both media influence and social/interpersonal influence are positively related to one another. The Malay women admitted that hijab wearing have much/very much changed them towards being good Muslims.